Emotion as interface and the cultural politics of synthetic empathy - Long, Bai (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
This paper investigates how emotion functions as an interface in artificial intelligence (AI)-mediated communication systems, with a critical focus on the cultural politics embedded in synthetic empathy. Drawing from affect theory, critical communication studies, and posthumanist perspectives, the study employs a qualitative, discourse-analytical approach to examine how emotional responsiveness is simulated, packaged, and operationalized in human-machine interactions. Empirical cases include AI-powered therapeutic bots, emotionally adaptive voice assistants, and automated customer service agents. The analysis reveals that synthetic empathy, rather than reflecting genuine emotional understanding, primarily serves as a mechanism for behavioral optimization aligned with neoliberal market logics. Emotion, when coded into technological interfaces, becomes a regulatory tool—modulating user engagement while concealing asymmetries in care, power, and agency. Furthermore, the cultural scripting of empathy in AI systems tends to reproduce dominant affective norms, marginalize non-normative emotional expressions, and depoliticize the labor of care, thus reinforcing structural inequities under the guise of affective neutrality. The contribution of this paper lies in its critical interrogation of emotional design as a site of power negotiation in digital systems, highlighting how affective interfaces participate in broader sociotechnical processes of commodification and control. By situating synthetic empathy within cultural, ethical, and political frameworks, the study offers a novel theoretical lens for understanding the implications of emotional AI. It calls for a reimagining of emotional mediation in AI that prioritizes cultural specificity, relational ethics, and the recognition of human vulnerability—thereby contributing to the development of more just and accountable communicative technologies in the digital age.